Notas sobre o planejamento urbano e regional em Iranduba/AM: percepções, conflitos, avanços e limites para implementação da REURB - QUARESMA, Ellen de Melo (2022)
This article is the result of initial reflections on the implementation of urban land regularization in the municipality of Iranduba, State of Amazonas, which recently joined the Programa Rede Amazônia: live, live e preserve, a partnership between the Land Regularization Commission of the Federal University of Pará (CRF-UFPA) and the Ministry of Regional Development (MDR). It is intended to discuss the socio-territorial formation of the municipality in order to reflect on its multipli(city) of occupation and consolidation of the urban nucleus and, thus, to think about the effectiveness of the REURB in the light of the understanding of the relations of the local social agents in the Amazonian territory, understanding the environmental specificities that mark the housing and sanitary conditions in the municipality. For the clipping of this wide universe of research, the systematic literature review was defined as a methodology for the analysis of secondary data.